Role of atropine in prevention of reflex bradycardia in response to awaked intubation in neonatal anesthesia - Ramadhan, Saeed G.; Salman, Iyad A.; Jabbar, Mohammad A. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Neonates (0–1 months) have different anesthetic requirements. Safe anesthetic management depends on full appreciation of the physiological, anatomic, and pharmacological characteristics of this age group. One of important difference in neonates is easy development of reflex bradycardia and cardiac standstill during anesthesia. These characteristics, differentiate them from adults, and necessitate modification of anesthetic equipment, medications, and techniques. Objectives: To evaluate the role of atropine in prevention of reflex bradycardia in neonatal anesthesia. Patients and methods: This is a prospective study done on 30 neonate patients in Baghdad teaching hospital/Baghdad /Iraq during the period from January - July/ 2009. Neonates that underwent major surgical operations, were randomly allocated into two groups, group (A) received atropine(0.015mg/kg) 5 minutes before awake intubation and group (B) (control group) received no atropine. Heart rate was recorded at pre-induction and during intubation then anesthesia was maintained in a similar way in both groups. Result: the results reported in this study indicate that the pre-induction with i.v. atropine was associated with a statistically significant decrease in the incidence rate of reflex bradycardia (below 100 beat/min or reduction in HR > 20% of basal heart rate) during intubation from 96.65% in the group (B) (control group) to 26.6 % in the group (A) (atropine group) In addition the magnitude of reduction in heart rate was lower by a mean of 22% in the atropine group compared to the mean reduction 41% in group (B Conclusion: Pre-induction with IV atropine decrease in the incidence of reflex bradycardia during intubation from 96.65% in the control group (B) to 26.6% in the atropine group (A). Pre-induction of atropine reduces the magnitude of heart rate reduction during intubation by a mean of 22% compared to 41% in control group.